2015
DOI: 10.1080/1750984x.2015.1052088
|View full text |Cite
|
Sign up to set email alerts
|

The yips in sport: A systematic review

Abstract: The yips are a psycho-neuromuscular movement disorder, which\ud affects sports in which fine motor precision skills are required for\ud success. This review aims to examine key components of the yips\ud within sport literature using a systematic approach. Twenty-five\ud published studies were used in the systematic review, the majority\ud of which focused on the yips in golf (n = 18); case studies were the\ud most popular methodological approach (n = 12). Four components\ud of the yips were identified: psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 59 publications
3
66
0
1
Order By: Relevance
“…To date, only two yips studies have reported a difference between yips-affected and unaffected golfers; Adler et al (2011) and Stinear et al (2006) reported that yips-affected athletes were significantly older than those unaffected athletes, suggesting that experience may be a pathway for yips development, and specifically that overuse of motor skills may act as one possible mechanism (Smith et al, 2003). However, analysis of the demographics also revealed no significant difference in experience or handicap, in golfers, between the two groups within each paradoxical performance, supporting that individuals of all levels and experience can suffer with these symptoms (Clarke et al, 2015). Only golfers' current handicaps were recorded which may not be the best indicator of ability as Adler et al (2011) reported that those golfers who reported experiencing the yips had a significantly lower best handicap than those non-affected.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…To date, only two yips studies have reported a difference between yips-affected and unaffected golfers; Adler et al (2011) and Stinear et al (2006) reported that yips-affected athletes were significantly older than those unaffected athletes, suggesting that experience may be a pathway for yips development, and specifically that overuse of motor skills may act as one possible mechanism (Smith et al, 2003). However, analysis of the demographics also revealed no significant difference in experience or handicap, in golfers, between the two groups within each paradoxical performance, supporting that individuals of all levels and experience can suffer with these symptoms (Clarke et al, 2015). Only golfers' current handicaps were recorded which may not be the best indicator of ability as Adler et al (2011) reported that those golfers who reported experiencing the yips had a significantly lower best handicap than those non-affected.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, predictors of both the yips and choking stemmed from social origins, but the specific traits were different in both. As the current study was based on subjective responses to having experienced paradoxical performance, further experimental testing of these paradoxical experiences is warranted in laboratory or ecologically valid (competition) settings under different social manipulations to see their role in yips and choking susceptibility (Lobinger et al, 2014;Clarke et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations